2017
DOI: 10.17645/pag.v5i4.1070
|View full text |Cite
|
Sign up to set email alerts
|

Dispute Settlement for Labour Provisions in EU Free Trade Agreements: Rethinking Current Approaches

Abstract: While labour provisions have been inserted in a number of EU free trade agreements (FTAs), extant clauses are widely perceived as ineffective. This article argues that there is a need to rethink the dispute settlement mechanisms related to labour provisions if their effectiveness is to be increased. It proceeds in three steps. First, we look at the current state of the art of labour provisions in EU FTAs in terms of legal design and practice and argue that the current arrangements are ill-equipped to foster co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Another approach is to use economic incentives as leverage to promote human rights (Hafner‐Burton, ; Marx et al., , ). The idea behind this is that countries and international organisations could tie material benefits to compliance by integrating human rights standards into an international agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to use economic incentives as leverage to promote human rights (Hafner‐Burton, ; Marx et al., , ). The idea behind this is that countries and international organisations could tie material benefits to compliance by integrating human rights standards into an international agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The case study by Oehri (2017) on the US FTAs complaint procedure is an example of the development of institutions. In this thematic issue, this is also addressed in the study by Marx, Ebert and Hachez (2017), which points to improvements in the dispute settlement mechanism in EU and US FTAs. The study by Kolben (2017), on the other hand, links a supply chain approach to FTAs, while Gansemans et al (2017) specifically analyse the supply chain of pineapples.…”
Section: Our Approachmentioning
confidence: 93%
“…Two articles in this thematic issue come with innovative ideas to adjust the FTAs. Marx et al (2017) study the dispute settlement mechanism of EU and US FTAs and arrive at the conclusion that elements of other instruments could help to fill the gaps in the current complaint and dispute settlement provisions, also by allowing more third (nonstate) parties acknowledgement. Kolben (2017) shows how labour standards could be improved by combining a supply chain approach with FTAs, creating a more tailormade instrument.…”
Section: Main Findingsmentioning
confidence: 99%
“…The dispute resolution mechanism is based on the promotional and monitoring methods that are prevalent in the ILO. Whilst this is more palatable from a political perspective, not least to EU partners, the literature examining TSD chapters and their implementation has suggested that without recourse to trade sanctions (withdrawal of preferences) these are unlikely to be effective (Lowe, 2019;Marx et al, 2017;Van Roozendaal, 2017). Turning to the EU-Korea TSD dispute in subsequent sections allows for an exploration of these claims.…”
Section: Trade and Sustainable Development Chapters In Eu Free Trade Agreementsmentioning
confidence: 99%